Interleukin-36 in Infectious and Inflammatory Skin Diseases - Buhl, Anna-Lena; Wenzel, Joerg (Frontiers in Immunology, 2019)
Interleukin 36 (IL 36) comprises to a cytokine family consisting of four isoforms IL 36, IL 36, IL 36, and IL 36 receptor antagonist (IL 36 Ra). These IL 36 cytokines, in turn, belong to the IL 1 superfamily. The IL 36 receptor (IL 1R6) is functional as a heterodimer formed of IL-1R6 and IL 1 receptor accessory protein (IL 1RAcP). IL 36, IL 36, and IL 36 are regarded as pro-inflammatory ligands and IL 36 Ra as well as IL-38 as anti-inflammatory ligands of IL 1R6. IL-36 cytokines are mainly expressed on the barrier sites of the body e.g. bronchial, intestinal and dermal epithelium. One of their most important biological functions is the bridging of innate and adaptive immune responses. A disturbed balance between pro-inflammatory and anti-inflammatory branches easily leads to inflammation of the corresponding tissue. The most prominent example for an altered IL-36 expression is the spectrum of psoriasis. In addition to inflammatory dermatoses, IL 36 also seems to play a role in infectious dermatoses. Microbial triggers, especially Staphylococcus aureus infection, increase the production of pro-inflammatory IL 36 cytokines and initiate/promote the inflammation of skin lesions. Due to the discovery of IL 36 as an important immune mediator, it has already been possible to develop important diagnostic tools for dermatitis. Not only in the field of inflammatory skin diseases, but also in pulmonary and intestinal inflammation, there is evidence that IL-36 cytokines might have diagnostic and/or therapeutic relevance.